A Pilot Study of ANXA2, MED12, CALM1 and MAPK1 Gene Variants in Primary Hyperparathyroidism - Chorti A; Achilla C; Siasiaridis A; Aristeidis I; Cheva A; Theodosios Papavramidis T; Chatzikyriakidou A (Balkan Journal of Medical Genetics)
Primary hyperparathyroidism (PHPT) is a common endocrine disorder characterized by the overactivity of the parathyroid glands. While a few genes have been linked to a predisposition for PHPT, the genetic foundation of the disease remains unclear, despite it being the third most prevalent endocrine disorder. This pilot study aimed to investigate, for the first time, the potential association between specific variants in Annexin A2 (ANXA2-rs7170178, rs17191344, rs11633032), Mediator Complex Subunit 12 (MED12-rs1057519912), Calmodulin 1 (CALM1-rs12885713), and Mitogen-Activated Protein Kinase 1 (MAPK1-rs1057519911) genes with PHPT. Previous expression analyses have indicated that the proteins related to these genes are involved in parathyroid adenomas or PTH signaling. Fifty unrelated PHPT patients and an equal number of healthy controls were enrolled in the study. Genotyping was conducted using the polymerase chain reaction - restriction fragment length polymorphism assay. Statistical analysis was performed to assess the connection between genetic variants and PHPT. Our results revealed no significant differences in genotypes’ or alleles’ distributions of any of the studied variants between PHPT patients and controls. These findings suggest that these variants may not be linked to PHPT in the studied population. This pilot study, focusing on a Caucasian group of PHPT patients, contributes to the existing genetic data for future meta-analyses, which will provide a more precise definition of the genetic factors associated with PHPT susceptibility worldwide.